2019
DOI: 10.1038/s41598-019-50692-1
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin signals via ATP and its effect is blocked by purinergic receptor antagonism

Abstract: Shiga toxin (Stx) is the main virulence factor of enterohemorrhagic Escherichia coli (EHEC), that cause gastrointestinal infection leading to hemolytic uremic syndrome. The aim of this study was to investigate if Stx signals via ATP and if blockade of purinergic receptors could be protective. Stx induced ATP release from HeLa cells and in a mouse model. Toxin induced rapid calcium influx into HeLa cells, as well as platelets, and a P2X1 receptor antagonist, NF449, abolished this effect. Likewise, the P2X antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…The inhibition of C3a, by normalizing VDAC and ATP5I levels, also limited mitochondrial functional alterations, which are instrumental to cell apoptosis. On the basis of our data, however, we cannot rule out the possibility that cytosolic ATP production and extracellular ATP release may be modulated in Stx2/LPS mice, possibly through C3a, as other groups have described [ 62 , 63 ]. These findings in experimental HUS are consistent with our previous data, which showed the detrimental role of C3a on podocytes, through mitochondrial dysfunction, in mice with diabetic nephropathy [ 32 ].…”
Section: Discussioncontrasting
confidence: 65%
“…The inhibition of C3a, by normalizing VDAC and ATP5I levels, also limited mitochondrial functional alterations, which are instrumental to cell apoptosis. On the basis of our data, however, we cannot rule out the possibility that cytosolic ATP production and extracellular ATP release may be modulated in Stx2/LPS mice, possibly through C3a, as other groups have described [ 62 , 63 ]. These findings in experimental HUS are consistent with our previous data, which showed the detrimental role of C3a on podocytes, through mitochondrial dysfunction, in mice with diabetic nephropathy [ 32 ].…”
Section: Discussioncontrasting
confidence: 65%
“…Cells were incubated with microvesicles, free Stx2 or PBS for a total of 3 h and 15 min, washed with PBS three times and incubated with Lhomopropargylglycine (HPG, 1:1,000) diluted in methioninefree RPMI medium (Gibco) for 45 min before protein synthesis was measured using the Click-iT HPG Protein Synthesis Assay Kit (Thermo Fisher Scientific) according to the manufacturer's instructions. In total, cells were exposed to Stx2 for 4 h. This time point was selected as a previous study showed that Stx localized to the ER after 2 h (Johansson et al, 2019). Protein synthesis measurements were carried out using Alexa Fluor 647 azide for CHO-Gb3 and CHO-control cells or Alexa Fluor 488 azide for HeLa cells and DLD-1 cells.…”
Section: Protein Synthesis Assaymentioning
confidence: 99%
“…ATP release mediates ATP signaling through purinergic receptor P2X, which in turn leads to Ca+ influx and cellular damage. Finally, it produces Shiga toxin containing microvesicle [ 202 ]. Shiga toxin mediates unfolded protein response mediated by ER and yields apoptosis for epithelial, lymphoid, and endothelial cells [ 203 ].…”
Section: Introductionmentioning
confidence: 99%